PEMANFAATAN INSTAGRAM SEBAGAI MEDIA PROMOSI UMKM MINUMES BENGKULU DALAM MENINGKATKAN KETERLIBATAN KONSUMEN - Ipan Julianto; Fitria Yuliani (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to analyze Minumes Bengkulu’s use of Instagram as a promotional medium and to identify the marketing communication strategies employed to increase consumer engagement. The study employs a descriptive qualitative approach involving five informants, comprising Instagram account managers, store managers, and active Minumes Bengkulu customers. Data were collected through in-depth interviews, observations, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. Data validity was ensured through triangulation of sources and methods. The results indicate that Instagram is utilized optimally through the use of photo posts, promotional videos, Instagram Stories, and Direct Messages (DMs) to foster interaction with consumers. The implemented promotional strategies focus on presenting visually appealing content, maintaining posting consistency, and engaging in two-way communication with customers. The research findings indicate that the utilization of Instagram features is capable of increasing consumer engagement, as demonstrated by high levels of response in the form of comments, direct messages, and interactions with uploaded content. In addition to serving as a promotional medium, Instagram also serves as a means of building closer relationships between businesses and customers. This study contributes to the development of research on digital marketing communication by demonstrating how social media can be utilized by SMEs to build consumer engagement through interactive communication strategies. In practical terms, the findings of this study can serve as a reference for SME operators in optimizing the use of Instagram as an effective and sustainable promotional medium. Keywords: Instagram, digital marketing communication, promotion, consumer engagement, SMEs.